Intelligent API Automation Framework for Enterprise Microservices: A Four-Layer Architecture for Governance, Orchestration, and Telemetry-Driven Optimization - Jyothirmai Gurramula (International Journal of Engineering, Science and Information Technology, 2026)
Enterprise microservices ecosystems have become central to modern financial and technology platforms, yet they introduce persistent governance challenges, including fragmented API contracts, undifferentiated traffic policies, siloed telemetry, and brittle workflow orchestration that can fail under load. Existing integration middleware typically addresses these concerns independently rather than through a coherent architectural model. This paper proposes the Intelligent API Automation Framework (IAAF), a four-layer reference architecture designed to systematically address these limitations. Layer 1, API Design and Governance, enforces schema-first contract discipline, automated lint validation, and lifecycle management across hundreds of microservice endpoints. Layer 2, Workflow Orchestration, coordinates multi-service transactions through declarative saga choreography, reducing dependency on distributed locking mechanisms. Layer 3, Decision Automation, integrates policy engines and machine learning-assisted routing logic within the gateway plane, enabling context-aware traffic shaping without requiring application-layer modification. Layer 4, Telemetry Optimization, combines structured logging, distributed tracing, and service-level-objective (SLO)-aligned alerting within a unified observability pipeline. Empirical validation using a financial services reference implementation demonstrates that IAAF reduces API governance violations by 73%, improves workflow completion rates by 68%, and decreases mean time to detect (MTTD) by 61% compared with baseline middleware configurations. These findings indicate that IAAF provides an integrated and practical architectural approach for operationalizing intelligent API automation at enterprise scale. The framework enables organizations to strengthen governance, improve transaction reliability, optimize traffic management, and enhance operational visibility while maintaining flexibility across complex microservices environments and supporting scalable digital transformation initiatives. The results further highlight its potential for resilient, scalable, and adaptive enterprise operations